The Removal of Residual Concentration of Hazardous Metals in Wastewater from a Neutralization Station Using Biosorbent-A Case Study Company Gutra, Czech Republic - Pertile, Eva; Vaclavik, Vojtech; Dvorsky, Tomas; Heviankova, Silvie (International journal of environmental research and public health, 2020)
This article deals with the possibility of using a biosorbent in the form of a mixture of cones from coniferous trees to remove the residual concentration of hazardous metals contained in hazardous waste, which is disposed of in a neutralization station. The efficiency of the tested biosorbent in removing Ni, Zn, Cu, and Fe was monitored here. Laboratory research was carried out before the actual testing of the biosorbent directly in the operation of the neutralization station. With regard to the planned use of the biosorbent in the operational test, the laboratory experiments were performed in a batch mode and for the most problematic metals (Ni and Zn). The laboratory tests with real wastewater have shown that the biosorbent can be used to remove hazardous metals. Under the given conditions, 96% of Ni and 19% of Zn were removed after 20 min when using NaOH activated biosorbent with the concentration of 0.1 mol L-1. The inactivated biosorbent removed 93% of Ni and 31% of Zn. The tested biosorbent was also successful during the operational tests. The inactivated biosorbent was applied due to the financial costs. It was used for the pre-treatment of hazardous waste in a preparation tank, where a significant reduction in the concentration of hazardous metals occurred, but the values of Ni, Cu, and Zn still failed to meet the emission limits. After 72 h, we measured 10 mg L-1 from the original 4,056 mg L-1 of Ni, 1 mg L-1 from the original 2,252 mg L-1 of Cu, 1 mg L-1 from the original 4,020 mg L-1 of Zn, and 7 mg L-1 from the original 1,853 mg L-1 of Fe. However, even after neutralization, the treated water did not meet the emission limits for discharging into the sewer system. The biosorbent was, therefore, used in the filtration unit as well, which was placed in front of the Parshall flume. After passing through the filtration unit, the concentrations of all the monitored parameters were reduced to a minimum, and the values met the prescribed emission limits. The biosorbent was further used to thicken the residual sludge in the waste pre-treatment tank, which contributed to a significant reduction in the overall cost of disposing of residual hazardous waste. This waste was converted from liquid to solid-state.
Keywords: odpad tekutý - odstraňování; nickel; chemické látky znečišťující vodu; iron; Wastewater; Water Pollutants, Chemical; neutralization station; Adsorption; Metals; Zinc; Waste Disposal, Fluid; kovy; odpadní voda; zinc; copper; zinek; hazardous waste; biosorption; desorption; těžké kovy; Czech Republic; Waste Water; Česká republika; Metals, Heavy; adsorpce